Parathyroid Hormone-Related Protein Overexpression Decreases Blood Pressure in Spontaneously Hypertensive Rats - Landa, Maria Silvina (2009)
We have recently demonstrated that arterial PTHrP expression and cardiovascular responses to this protein are altered in SHR compared with normotensive animals, Wistar Kyoto (WKY) and Sprague-Dawley (SD) rats. To investigate whether the slightly, but significantly decreased, aortic PTHrP gene expression observed in SHR, compared to that of normotensive animals, may play a causative role in the maintenance of the elevated arterial blood pressure (ABP) of the SHR, we transfected a hepatic lobe with a PTHrP expression vector in a sense and antisense orientation. At 24 and 48 hours, sense pSV2neo-ECE induced a significant five-fold increase in PTHrP mRNA abundance with respect to antisense pSV2neo-ECE and vehicle. This increment in the PTHrP mRNA induced by the sense PTHrP expression vector was totally inhibited by the co-administration of the antisense PTHrP expression vector. At the same time, we observed a significant decrease of mean ABP (MABP) in SHR transfected with the sense pSV2neo-ECE to similar values as those obtained in the normotensive strain. Neither antisense PTHrP expression vector nor vehicle had any significant effect in any strain. Again, the effect of the sense PTHrP expression vector on MABP was blocked by the simultaneous treatment with the antisense PTHrP expression vector. At 48 hours, the hypotensive effect of the sense pSV2neo-ECE in SHR was reverted by the IV bolus injection of a specific competitive PTHrP receptor antagonist such as Nle8,18,Tyr34-bPTH(3–34)amide. We propose that a defect of this potent local vasodilator may contribute to the development and/or maintenance of arterial hypertension in SHR. This defect can be ameliorated by transfecting tissues with protein-exporting capabilities, such as the liver. Finally, our work adds additional data to a cumulative body of evidence suggesting that it might be possible to design an effective gene therapy to treat the common polygenic and multifactorial form of hypertension by increasing the activity of potent and physiological vasodilators.